A new species of the genus Sphedanolestes Stål 1866 (Hemiptera: Reduviidae: Harpactorinae) from China, with a key to Chinese species - Zhao, Ping; Ren, Shuzhi; Wang, Baohai; Cai, Wanzhi (Zootaxa, 2015)
A new harpactorine bug, Sphedanolestes zhengi sp. nov., is described and illustrated based on specimens collected from southwestern China. A key to 17 Chinese species of the genus, including the new species, is provided. The bionomics of the new species is briefly noted.